Er kirkelig polemik nedbrydende? - Baagø, Kaj (Grundtvig-studier, 1957)
Is Religious Controversy Destructive? A Discussion between Grundtvig and Nicolai Faber in 1825. By Kaj Baagø. Not many of the letters written by Grundtvig in the autumn of 1825 (when the conflict in the Danish Church — the great “settling of accounts” with rationalism — was at its height) have been preserved. The conflict had already begun in the spring in “ Theologisk Maanedsskrift” (“ The Theological Monthly”), published by Grundtvig and his friends. In it Grundtvig reviewed some sermons by Nicolai Faber — at that time a parson, later bishop in Fyn —, and this led to an exchange of views between the two of them. First Faber published “ Five Letters to the Reverend N. F. S. Grundtvig”, in which he sough to show that Grundtvig’s general criticism of the theology of the eighteenth century was unjustified and extremely one-sided. Grundtvig answered him privately in a letter (I) and expressed his annoyance that Faber had answered his comparatively kind review in such a fashion. On account of the great controversy with Professor Clausen in these months he did not wish to reply publicly and thus bring confusion into the main “battle”. — In au long letter (II) Faber then defended his mode of action, and tried at the same time to clear up his difference with Grundtvig. While Grundtvig wished to bring about the triumph of truth by sharply attacking unbelief and demanding unconditional belief, Faber desired another method of procedure. It was necessary to awaken “the spirit” in the unbeliever, so that he would feel there is something higher than himself and would gradually be awakened to new faith. Grundtvig’s polemics only awakened doubt in the layman, and contempt for the clergy and theological professors. He quoted examples from “ Theologisk Maanedsskrift” and ended with a plea that there migh be an end of harsh controversy in that periodical. To this Grundtvig replied (III) with an immensely long letter (exceedingly unusual in that period in his life). The controversy is not about scholarly themes, but about the faith of the people. The rationalistic clergy have in course of time got the people lulled to sleep, and, if they are to be awakened, controversy is needed to do this. And it is also necessary to attack individuals, e. g., the professors, whom the students worship in their blindness, so that their rationalism may be laid bare. How would it have fared with the Reformation, Grundtvigs asks, if Luther and his friends had taken to discussing dogmatics nicely instead of attacking the corrupted clergy and the corrupted Papacy in the boldest way? Now — in “the second Reformation” — controversy is also necesssary, and in the hope that Faber will be able to perceive this, he concludes with best wishes.